Analysis of the Consumer Perceptions of Online Shopping: Case of Bangladesh - Karim, B. M. Sajedul; Rahman, Md. Mostafijur; Billah, Md. Rashed; Nurunnahar; Khatun, Most. Tania; Hasan, Md. Imran; Bodepudi, Anusha; Reddy, Manjunath (Asian Business Review, 2023)
Though online shopping has become a new type of retail shopping, it has been adopted worldwide, including in Bangladesh, influencing ordinary citizens' lives. In Bangladesh, consumers have not been habituated to online shopping frequently. This study aims to identify consumer perceptions of online shopping in Bangladesh. The study has 140 sample sizes from the Chuadanga district by forming a self-structured closed-ended Questionnaire. The SPSS version 16.0 statistical tool is used in this study. Several statistical tools, like frequency tests and percentages, were used to measure the objective. We found that consumers are primarily young, below 30 ages, who shop online to save time, and for available varieties of products and services and prefer to pay through cash on delivery method. Most consumers feel risk in online shopping and are also concerned about the security of the payment system. Overall, Consumers are satisfied with online shopping. Also, this study has a few limitations. Future research with a larger sample size and additional variables is recommended.